Muraymycin Nucleoside Antibiotics: Structure-Activity Relationship for Variations in the Nucleoside Unit - Heib, Anna (Molecules, 2019)
Muraymycins are a subclass of naturally occurring nucleoside antibiotics with promising antibacterial activity. They inhibit the bacterial enzyme translocase I (MraY), a clinically yet unexploited target mediating an essential intracellular step of bacterial peptidoglycan biosynthesis. Several structurally simplified muraymycin analogues have already been synthesized for structure–activity relationship (SAR) studies. We now report on novel derivatives with unprecedented variations in the nucleoside unit. For the synthesis of these new muraymycin analogues, we employed a bipartite approach facilitating the introduction of different nucleosyl amino acid motifs. This also included thymidine- and 5-fluorouridine-derived nucleoside core structures. Using an in vitro assay for MraY activity, it was found that the introduction of substituents in the 5-position of the pyrimidine nucleobase led to a significant loss of inhibitory activity towards MraY. The loss of nucleobase aromaticity (by reduction of the uracil C5-C6 double bond) resulted in a ca. tenfold decrease in inhibitory potency. In contrast, removal of the 2′-hydroxy group furnished retained activity, thus demonstrating that modifications of the ribose moiety might be well-tolerated. Overall, these new SAR insights will guide the future design of novel muraymycin analogues for their potential development towards antibacterial drug candidates.